Measuring information security policy compliance: content validity of questionnaire - Angraini Angraini; Rose Alinda Alias; Okfalisa Okfalisa (Institute of Advanced Engineering and Science, 2021)
Instruments used to measure compliance with information security policies have been developed by many researchers before, but only a few have conducted validity tests per item, especially for variables selected based on qualitative research. This study aims to validate the questionnaire will be used to measure user compliance with policies of information security. This study began by designing a questionnaire and conducting content validation using content ratio validation (CVR) and content index validation (CVI). As many as eight experts from the university assessed the items given. The results of 72 items submitted a questionnaire, as many as 22 items eliminated, and only 50 items that have CVR and CVI values above 0.75. Also, Kappa statistical calculations show that items have excellent reliability among assessors at the item level. This study revealed that this instrument had obtained an appropriate level of validity to measure compliance with information security policies.